2000
DOI: 10.1177/0310057x0002800306
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of PVC Packaging on the Acidity of 0.9% Saline

Abstract: Intravenous fluids in polyvinyl chloride (PVC) packaging are known to be acidic. We proposed to determine the effect of PVC packaging on the pH of 0.9% saline solutions by comparing the predicted and measured pH of 0.9% saline equilibrated with atmospheric carbon dioxide and the measured pH of commercial solutions of 0.9% saline in PVC and polypropylene packaging. Calculation of pH was made from available physical chemistry constants and data. Measurement was made of the pH of 12 samples of prepared 0.9% salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Normal saline (0.9%) has an average pH of 5 and potentially as low as 4.6. 31 Ringer's lactate has an average pH of 6.5, with similar electrolytes as plasma. 32 Maroudas also described the electrolyte activity of articular cartilage as similar to that of Ringer's solution.…”
Section: Ringer's Solution and Ringer's Lactate Vs Normal Salinementioning
confidence: 99%
See 1 more Smart Citation
“…Normal saline (0.9%) has an average pH of 5 and potentially as low as 4.6. 31 Ringer's lactate has an average pH of 6.5, with similar electrolytes as plasma. 32 Maroudas also described the electrolyte activity of articular cartilage as similar to that of Ringer's solution.…”
Section: Ringer's Solution and Ringer's Lactate Vs Normal Salinementioning
confidence: 99%
“…42 Increased osmolarity leading to chondroprotective effects is a conclusion that most of the included studies agreed with. 25,[28][29][30][31] Previous studies have also demonstrated that after mechanical injury to the articular cartilage, a decrease in extracellular osmolarity resulted in more extensive chondrocyte death compared with a higher osmolarity. 43,44 One study found that during drilling, chondrocyte death was significantly reduced by raising osmolarity and reducing Ca2+ content.…”
Section: Osmolaritymentioning
confidence: 99%
“…Studies comparing (i) the theoretical pH of saline derived using the principles outlined above, (ii) the pH of saline prepared in the laboratory in the absence of PVC, and (iii) clinical grade saline from a widely used commercial source packaged in PVC based material revealed that whilst prepared samples had a very similar pH to that predicted (median 5.47), the median pH of the PVC packaged saline was 4.6. Interestingly, the pH of saline in polypropylene packaging was 5.71, suggesting a particular property of PVC to be culpable 1. Of interest, concerns that constituents and degradation products of PVC/DEHP packaging might have endocrine disrupting effects have meant that polyethylene and polypropylene containers for intravenous solutions are increasingly favoured in their stead10.…”
Section: Degradation Products Of Pvc Packagingmentioning
confidence: 99%
“…In fact it is quite acidic: pH being reported as low as 4.6 1. Why does this simple solution have a pH so far removed from the physiology it is designed to support?…”
Section: Introductionmentioning
confidence: 99%
“…0.9% saline is in reality a non-neutral solution (12) and has a supraphysiologic amount of chloride when compared to plasma (154 vs ~100 mEq/L, respectively) (13, 14). The consequent hyperchloremic metabolic acidosis derived from the liberal use of chloride-rich solutions has been described as a common but poorly recognized disorder in critically ill patients (15, 16), with numerous detrimental consequences (17, 18), particularly in those with severe sepsis and septic shock (19).…”
Section: Introductionmentioning
confidence: 99%